Eksistensi Penegakan Hukum Lingkungan Dalam Mewujudkan Pertumbuhan Ekonomi dan Pembangunan Berkelanjutan di Indonesia - Intan Wahyuningtyas Andin; Muhammad Danda Evantrino; Romadona Putri Pertiwi (Pusat Riset dan Inovasi Nasional, 2025)
This article discusses the increasing environmental challenges in Indonesia and the need for environmental law enforcement to maintain the sustainability of the planet. The problem of environmental pollution and degradation has become a major concern, requiring shared responsibility to overcome its impacts. Loss of wetlands, depletion of forests, as well as floods and landslides increasingly reinforce the need for comprehensive preventive and rehabilitation measures. One of the biggest threats is forest fires, which are becoming more frequent and threatening ecosystems. Enforcement of environmental laws is important to ensure environmental protection, in accordance with constitutional values that affirm the right of every individual to a healthy environment. In its discussion, this article highlights the importance of environmental law enforcement in encouraging sustainable economic growth in Indonesia. Effective law enforcement can create conditions that support development planning and implementation in all sectors. Apart from that, the article also illustrates the relationship between environmental legal concepts and economic growth, which are interrelated in ensuring that economic activities are carried out with due regard to sustainability principles. The concept of environmental law helps prevent excessive environmental damage and creates new opportunities in the green economy. In addition, this article discusses the contribution of environmental law to sustainable development, emphasizing the importance of integrating environmental, social and economic aspects in development strategies. Sustainable development is defined as a conscious and planned effort to ensure the integrity of the environment and the welfare of present and future generations. In this context, the role of environmental law becomes very important in ensuring the sustainability of ecosystems and overall human welfare.